Loneliness, coping strategies and perceived social support among students of public universities in Malaysia during the COVID-19 MCO - Hussin, Siti Haslina; Awang Daud, Awang Ideris; Taibi, Malia; Hussin, Siti Rahayu (Faculty of Economics and Business, Universiti Malaysia Sarawak, 2021)
The unprecedented COVID-19 pandemic had prompted many governments to enforce lockdown to prevent the virus from spreading. In Malaysia, a series of Movement Control Orders (MCO) were introduced starting March 18, 2020. As a result, many people’s lives were affected, including university students. These affected students had to stay in their campus residential facilities, isolated from family, relatives and friends, which could lead to the feeling of loneliness. This study aims to explore the phenomenon among students stranded on campus during MCO periods. Approximately 243 students from several public universities were surveyed using Google form. Results from the 210 usable responses showed that most of these students experienced moderate loneliness and often used coping approaches like acceptance, positive interpretation, active coping, and active solitude. Friends seemed to be a more immediate source to seek for support in times of isolation. Correlation results suggested that social support availability is negatively associated with student loneliness experience, and positively related with student coping strategies. Specifically, the availability of support from friends and significant others may minimize loneliness experience.